Evaluacion de la variabilidad en los principales tipos de melon cultivados en España - Costa, J.=700 1 Catala, M.S.; Cortes, C.; Nuez, F.; Abadia, J.; Cuartero, J.
(En, Es)
ilus., 5 ref.
Keywords: CUCUMIS MELO; VARIACION GENETICA; GERMOPLASMA; ESPAÑA